Small states in the perfect storm: crisis management and economic credibility in Ireland’s and Iceland’s financial crises - Carstensen, Martin B. (Politica, 2016)
Despite having lived through some of history’s greatest financial and economic crises, the two small open economies of Iceland and Ireland are now enjoying relatively high growth rates and declining unemployment, and are broadly regarded as success stories of effective economic turnarounds. In both countries, policy focused on restoring the confidence of international capital markets, but whereas Icelandic crisis management has compensated the people worst hit by the crisis through socially balanced austerity and debt cancellation, Ireland’s austerity followed a more orthodox, European approach with significant inequality-creating effects. Iceland’s heterodox approach was made possible through capital controls and a devaluation of the currency, while Ireland could neither devalue nor write down bank debt. The article shows how the dependence on international capital markets and the abandonment of independent monetary policy restrict the flexibility small states have previously enjoyed and increase dependence on fortunate developments in the world economy.